Distinguishing profiles of adversity among child protection investigations in Ontario, Canada: A latent class analysis - Rachael Lefebvre; Barbara Fallon; John Fluke; Nico Trocmé; Tara Black; Tonino Esposito; David W. Rothwell (Child Protection and Practice, 2024)
Background: Child welfare-involved families have diverse and multi-faceted needs. Families who experience poverty and are investigated by the child protection system may represent a particularly vulnerable group. Objective: This study aims to understand the unique profiles of need that exist for families who experience poverty and are investigated by the Ontario child protection system. Participants and setting: Data from the Ontario Incidence Study of Reported Child Abuse and Neglect 2018 (OIS-2018) was used. The OIS-2018 is a cross-sectional study which collected information on investigations conducted in Ontario, Canada in 2018. Methods: A latent class analysis was conducted to identify and describe distinct classes of adversity among a representative sample of child protection investigations. Indicators of child, caregiver and economic adversity were used. Results: This study found evidence for eight distinct classes of adversity. With the exception of a low adversity class which emerged, the identified classes were characterized by distinct profiles of cooccurring adversities and there were several classes where indicators of poverty were probable. Investigation dispositions varied greatly by class. Conclusions: The findings highlight the importance of ensuring an optimal fit between the distinct needs of investigated families and the child welfare interventions provided. Services and supports that are tailored to the specific constellations of cooccurring adversities that families face may be more effective in reducing the need for future child welfare involvement and/or more intrusive child protection responses. It is likely that investigated families who experience poverty would benefit from a range of economic and concrete supports.